Newcastle Disease Virus Inhibits the Proliferation of T Cells Induced by Dendritic Cells In Vitro and In Vivo - Nan, Fu Long; Zheng, Wei; Nan, Wen Long; Yu, Tong; Xie, Chang Zhan; Zhang, He; Xu, Xiao Hong; Li, Cheng Hui; Ha, Zhuo; Zhang, Jin Yong; Zhuang, Xin Yu; Han, Ji Cheng; et al. (Frontiers in Immunology, 2021)
Newcastle disease virus (NDV) infects poultry and antagonizes host immunity via several mechanisms. Dendritic cells (DCs) are characterized as specialized antigen presenting cells, bridging innate and adaptive immunity and regulating host resistance to viral invasion. However, there is little specific knowledge of the role of DCs in NDV infection. In this study, the representative NDV lentogenic strain LaSota was used to explore whether murine bone marrow derived DCs mature following infection. We examined surface molecule expression and cytokine release from DCs as well as activation of T cells in vivo and in vitro in the context of NDV. The results demonstrated that infection with lentogenic strain LaSota induced a phenotypic maturation of immature DCs (imDCs), which actually led to curtailed T cell responses. Upon infection, the phenotypic maturation of DCs was reflected by markedly enhanced MHC and costimulatory molecule expression and secretion of proinflammatory cytokines. Nevertheless, NDV-infected DCs produced the anti-inflammatory cytokine IL-10 and attenuated T cell proliferation, inducing Th2-biased responses. Therefore, our study reveals novel understanding that DCs are phenotypically mature but dysfunctional in priming T cell responses during NDV infection.